THE INFLUENCE OF DANCING ACTIVITIES ON CHILDREN'S GROSS MOTOR SKILLS IN GROUP B OF KINDERGARTEN AISYAH CIKOLE SUKABUMI - Budi Utami, Fitria; Elnawati, Elnawati; Zain bin Musa, Muhamad (Penerbit Lafadz Jaya, 2023)
The sensitive period in children is when physical and mental abilities are experienced, children can respond to every stimulus given by the environment around the child. In the development of each child, every child is different because each child has their uniqueness. It is during this difficult time that the development and improvement of each child requires special attention to all aspects of progress, including the improvement of machinery. Improved motor skills are the most common way to create development in children, both in the development of finely coordinated abilities and gross coordinated movements. Gross motor improvement requires proper feeling. Therefore, in research using quantitative methods, experiments aim to apply dance activities so that children's gross motor skills in group B can increase. This was done based on initial findings that in TK Aisyiyah 2 Sukabumi City, children's gross motor skills were still low, where in every rhythmic gymnastics activity and when play activities were carried out, children were still carried out heavily, not yet seen agile.